56.9k views
0 votes
Evaluate (2 - 3)4(4) - 9 ÷ 3.

User Dattatray
by
3.9k points

2 Answers

4 votes

Answer:

-19

Explanation:

Simplify the following:

(2 - 3) 4×4 - 9/3

The gcd of -9 and 3 is 3, so (-9)/3 = (3 (-3))/(3×1) = 3/3×-3 = -3:

(2 - 3) 4×4 + -3

2 - 3 = -1:

-1×4×4 - 3

-4×4 = -16:

-16 - 3

-16 - 3 = -(16 + 3):

-(16 + 3)

16 + 3 = 19:

Answer: -19

User Sachin Kelkar
by
5.6k points
2 votes

Answer:

the edge answer is 1 i had trouble finding it so i put it myself

Explanation:

User Zack Katz
by
4.8k points